Integrasi pendidikan humanis dalam konteks pendidikan modern dan Islam di Indonesia: Pendekatan teoritis dan praktis - Ariyani, Nafiska Sayekti (Maliki Interdisciplinary Journal, 2024)
Humanist education places humans at the center of the educational process, with a focus on developing individual potential holistically. This article discusses the foundations of humanist education rooted in progressivism, constructivism, and existentialism, as well as the contributions of figures such as John Dewey, Jean Piaget, and Paulo Freire in developing this concept. The main goal of humanist education is to form critical, creative, and social awareness, with implementation involving educators as facilitators and creating a supportive learning environment. In the context of Islam, the concept of humanist education reflects the idea of ​​khalifatullah and emphasizes the development of student potential according to Islamic values. Although education in Indonesia still faces various challenges, the right transformation of education can create quality human resources. Humanist education is expected to restore the essence of education in humanizing humans and creating an inclusive learning environment.